Penerapan Analisis SWOT dalam Menentukan Strategi Pemasaran Syariah Produk Butik Maura Pacet Mojokerto - Hifi Rini Puspita (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2023)
The application of Islamic Shari'a in Mojokerto has developed a new paradigm regarding the application of law, including muamalah which causes the application of sharia principles in marketing to also be an interesting matter to study. This study aims to analyze the implementation of sharia marketing at the Butik Maura Pacet Mojokerto. Marketing mix variables consist of product, price, promotion and distribution, as well as SWOT variables. The method used is qualitative descriptive analysis approach. Sources of data obtained by observation, interviews, and documentation. The results of this study indicate that the implementation of the marketing mix has been carried out properly and in accordance with sharia principles, and there are no elements that deviate from Islamic law in the marketing process according to the example of the Prophet.